Challenges and way forward for implementing green roof in construction industry in Sarawak, Malaysia / Nurul Nabilah Abdul Rahim ...[et.al.] - Abdul Rahim, Nurul Nabilah; Mohamad Bohari, Asmah Alia; Adnan, Amira Shazlin; Khalil, Natasha; Olanipekun, Ayokunle Olubunmi (UiTM Press, 2021)
There is a growing global concern about the adverse effects of today's rapid economic growth and development, which impact the environment and deplete energy supply. A green roof may lower a building's energy consumption and minimise air pollution by reducing dust particles in the air. The primary impediment to green roof implementation in Malaysia lacks local knowledge and unskilled green roof specialists. As a result, there is a shortage of green roof installers and specialised firms in the country. This article discusses the problems and solutions of adopting green roofs in building projects based on construction industry experience in Sarawak. A survey utilising a questionnaire is used to obtain data for this research. The paper revealed the possible challenges of adopting a green roof for the construction industry. The study is critical in order to adopt green roof technology quickly in Malaysia.